Interpreting America in the Works of Knut Hamsun and Johannes V. Jensen - Vincent Rasmussen (Nordlit: Tidsskrift i litteratur og kultur, 2020)
The USA had an significant influence on the Nobel Prize-Winning authors Johannes V. Jensen and Knut Hamsun. Both authors spent significant amounts of time in America and subsequently expressed their thoughts and opinions on the country in the form of books and articles. Their diverging views on the topics of technological advancements and America’s future role in the world, serve to capture a small but significant part of the larger debate on America’s role in the Nordic countries in the early 20th century